2022
DOI: 10.18632/aging.203834
|View full text |Cite
|
Sign up to set email alerts
|

Association between tocilizumab treatment and clinical outcomes of COVID-19 patients: a systematic review and meta-analysis

Abstract: To explore and summarize the association between treatment with tocilizumab and clinical outcomes in COVID-19 patients. We performed a systematic review and meta-analysis (10 RCTs including 3378 patients in the tocilizumab group and 3142 patients in the control group). We systematically searched PubMed and MedRxiv for all RCTs as of June 1, 2021, to assess the benefits and harms of tocilizumab to treat patients with COVID-19. All analyses were carried out using RevMan version 5.4.1. There were nine RCTs publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
6
1
Order By: Relevance
“…The mortality rate found in the present study was relatively higher compared to the rates demonstrated in randomized controlled trials of tocilizumab and in meta-analyses mentioning a pooled mortality prevalence of 20-30% (17)(18)(19)(20)(21). One of the main findings of the present study was that among all patients treated with tocilizumab for COVID-19-associated pneumonia, age was the only independent factor predicting 90-day mortality.…”
Section: Discussioncontrasting
confidence: 68%
“…The mortality rate found in the present study was relatively higher compared to the rates demonstrated in randomized controlled trials of tocilizumab and in meta-analyses mentioning a pooled mortality prevalence of 20-30% (17)(18)(19)(20)(21). One of the main findings of the present study was that among all patients treated with tocilizumab for COVID-19-associated pneumonia, age was the only independent factor predicting 90-day mortality.…”
Section: Discussioncontrasting
confidence: 68%
“…44 Similarly, a recent systematic review and meta-analysis of clinical trials reported no significant associations between treatment with tocilizumab and reductions in all-cause mortality in COVID-19 patients. 45 Our observations and these studies together suggest that IM treatment is avoidable in CAPA as well as non-CAPA patients.…”
Section: Discussionsupporting
confidence: 60%
“…A number of randomised clinical trials have been conducted on the efficacy of IM (tocilizumab), including one at our institute, but its benefit is not yet clear 44 . Similarly, a recent systematic review and meta‐analysis of clinical trials reported no significant associations between treatment with tocilizumab and reductions in all‐cause mortality in COVID‐19 patients 45 . Our observations and these studies together suggest that IM treatment is avoidable in CAPA as well as non‐CAPA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of Tocilizumab in COVID-19 have given conflicting results, which may reflect lack of standard protocols for its use [ [16] , [17] , [18] , [19] , [20] ]. Initial trials demonstrated no clear benefit of Tocilizumab monotherapy on survival, length of hospital stay, need for mechanical ventilation, disease progression or time to recovery [ [21] , [22] , [23] , [24] , [25] , [26] ].…”
Section: Discussionmentioning
confidence: 99%